Decreased Bdnf expression and reduced social behavior in periadolescent rats following prenatal stress. Issue 3 (18th March 2015) - Berry, Alessandra; Panetta, Pamela; Luoni, Alessia; Bellisario, Veronica; Capoccia, Sara; Andrea Riva, Marco; Cirulli, Francesca
ABSTRACT: Prenatal stress (PNS) is a risk factor for the development of neuropsychiatric disorders. This study was aimed at assessing, in a rodent model, changes in gene expression profiles and behavioral output as a result of PNS, during periadolescence, a critical developmental period for the onset of psychopathology. Social behavior was studied in a standardized social interaction paradigm and the expression of Brain‐Derived Neurotrophic Factor ( Bdnf ), a marker of neuronal plasticity, and of inhibitory and excitatory mechanisms (Na + –K + –2Cl − and K + –Cl − cotransporters ratio, NKCC1/KCC2 ) was analyzed. Results indicate that PNS reduced Bdnf transcripts while increasing the NKCC1/KCC2 ratio, primarily in the hippocampus. In the prefrontal cortex, changes in Bdnf were found to be gender‐dependent. These effects were accompanied by reduced levels of affiliative and investigative social behaviors. Interestingly, interaction with non‐stressed subjects was able to improve sociality in PNS rats suggesting that the social environment could be exploited for therapeutic intervention. © 2015 Wiley Periodicals, Inc . Dev Psychobiol 57: 365–373, 2015.